Comparative Employment Relations France, Germany and Britain - Milner, Susan (New York Palgrave, 2015)
"Explores employment relations in three key European countries: France, Germany and the UK. The comparative approach examines key areas of employment relations to analyse national differences and similarities. This comparative text fills the gap between single country studies of employment relations and more broad-brush multi-country approaches"--
Machine generated contents note: -- 1. Introducing Comparative Employment Relations -- 2. Understanding Variety and Change in Capitalist Economies -- 3. The Changing Role of the State in Employment Relations -- 4. Trade Unions in and Beyond the Workplace -- 5. Does Collective Bargaining Still Matter? -- 6. Employment Relations in the Workplace: Voice, Representation and Conflict -- 7. Organisational Restructuring and Employment Relations -- 8. Working Time, Employment Regimes, and Employment Relations -- 9. Pay, Productivity and Skills -- 10. Conclusion: Lessons from Comparative Employment Relations.
Keywords: France, Germany and Britain; Industrial relations -- France; Industrial relations -- Germany; Industrial relations -- Great Britain; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Labor; POLITICAL SCIENCE / Labor & Industrial Relations